Floating, Flexible Polymeric Dye‐Sensitized Solar‐Cell Architecture: The Way of Near‐Future Photovoltaics. Issue 2 (13th April 2016) - Bella, Federico; Lamberti, Andrea; Bianco, Stefano; Tresso, Elena; Gerbaldi, Claudio; Pirri, Candido Fabrizio
Abstract : Light‐cured polymer‐based flexible dye‐sensitized solar cells with a patterned "Fakir"‐shaped super‐hydrophobic architecture on the external sided are demonstrated for the first time as truly floating photovoltaic devices. Conversion efficiency exceeding 5% and stable performance upon severe and very long‐term thermomechanical aging tests are obtained. The polymeric architecture paves the way to floating third‐generation photovoltaic devices (both dye‐sensitized and perovskite solar cells). It is therefore possible to avoid not only the overheating of cells and water evaporation from water bodies in the driest areas, but also the installation of photovoltaic systems on land, thus reserving land use for agriculture or building. Abstract : New‐generation solar cells float on water . A new approach is proposed that merges photopolymerization, microfluidics, and patterning of polymeric materials to create transparent, flexible, stable, and floating dye solar cells. The resulting technology represents an excellent alternative to the occupation of land by energy‐conversion systems.